A Genre Pedagogy for Teaching Young EFL Learners of English Village of Parit Baru - Aunurrahman Aunurrahman; Citra Kusumaningsih; Sahrawi Sahrawi; Maliqul Hafis; Emi Emilia (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This case study aimed to find out the implementation of a genre pedagogy under systemic functional linguistics (SFL) framework or under Sydney School to teach the English language to young English as a Foreign Language (EFL) learners of English Village of Parit Baru, Kubu Raya, West Kalimantan. Fifty-two young EFL learners were involved in this study. The data collection used two instruments, namely participant observations and documentation. The data analysis reveals that genre pedagogy elements could help the young EFL learners in constructing and communicating their texts independently. Also, the learners’ texts are following the schematic structures and linguistic features of the spoken genres the learners learned. To help the learners to cope with the teaching activities, songs and games activities were used to build their interest in the English language, new vocabulary, and practices to communicate their texts. This means that a genre pedagogy under the SFL framework could be integrated with joyful activities that not only provide guidance but also promote enjoyable learning in building the English language capacities of the young EFL learners in a non-formal educational context.